Association between Clinical Manifestations and Candida Carriage in Patients with Oral Sub-Mucous Fibrosis: Clinical Manifestations and Candida Carriage in Patients with Oral Sub-Mucous Fibrosis - Zain-Ul Abedeen, Muhammad; Rafiq, Muhammad Talal; Kanju, Abid Hussain; Liaqat, Sahrish; Abi Waqas, Muhammad; Riaz, Muhammad Mashood (Pakistan Journal of Health Sciences, 2024)
A chronic, progressive disorder known as oral sub-mucous fibrosis causes the oral mucosa to become inflamed and fibrotic, which limits mouth opening, causes a burning sensation, and reduces salivary flow. Objectives: To assess the relationship between candida carriage in oral sub-mucous fibrosis patients and demographic traits, tobacco use, and clinical parameters such as burning sensation, salivary flow rate, and mouth opening. Methods: A comparative cross-sectional study was conducted from May 2024 to Oct 2024. This study was conducted in Multan Medical and Dental College. The total number of patients was 384 divided into 192 with oral sub-mucous fibrosis and 192 control participants split into groups with and without risk exposure. Clinical characteristics such as mouth opening, salivary flow rate, and burning sensation (measured using a visual analogue scale) were evaluated. Data were analyzed with descriptive, mean, Post Hoc analysis, and Chi‑square tests. Results: Comparing the oral sub-mucous fibrosis positive group (93%) to the negative group (7%), the oral sub-mucous fibrosis group had a considerably greater prevalence of candida carriage. Reduced salivary flow rate (≤0.2 ml/min), restricted mouth opening (≤20 mm), and severe burning sensation (3-5 (Visual Analogue Scale)) were shown to be strongly correlated with candida positivity (p<0.001). A greater prevalence of candida colonization was also seen in patients who used tobacco more frequently (p<0.001). Conclusions: It was concluded that comprehensive treatment methods should include patient education on oral hygiene and quitting smoking, given the major impact that these behaviours play in candida's carriage.